Comparative study of Her-2, p53, Ki-67 expression and clinicopathological characteristics of breast cancer in a cohort of northern China female patients. Issue 4 (4th July 2017) - Ding, Li; Zhang, Zijin; Xu, Yan; Zhang, Yongqiang
ABSTRACT: The objective was to study the relationship among Her-2, Ki-67, p53 expression and the clinicopathologic characteristics of breast cancer in the patients of northern China. Expression of Her-2, Ki-67, p53 and clinical characteristics of 260 breast cancer patients were retrospectively studied. Her-2 overexpression led to higher incidence rates of infiltrating ductal carcinoma and axillary lymph node metastasis, bigger diameters of the primary tumors, later pTNM staging, and a lower incidence rate of ductal carcinoma in situ (p < 0.05). High expression of ER and PR led to fewer patients classified histologically in higher grade (p = 0.001), while high expression of Ki-67 and p53 caused more patients classified histologically in higher grade (p = 0.001). In patients histologically classified in grade 1 and 2, the expression of Ki-67 and p53 was significantly (p = 0.001) higher, and the expression of ER and PR was significantly lower, in Her-2 positive patients than Her-2 negative patients. Breast cancer with Her-2 overexpression was more likely to recur and metastasize than Her-2 negative breast cancer. Higher coincidence of high expression of p53 and Ki-67 with Her-2 overexpression and more progressed tumors suggested that in addition to p53, Ki-67 might also be a prognostic biomarker of breast cancer.